ANALISIS CHANNELING PADA SUMUR MINYAK MENGGUNAKAN CEMENT BOND LOG-VARIABLE DENSITY LOG - Patik, Diete
Cementing is basically held to strengthen the bond between casing and formation, which is useful to isolate formation and wellbore. Though, cementing doesn’t always seem to be perfect. Some problems exist, such as channeling; the condition where cement fills only some parts between casing and wellbore so that cement won’t get maximum hydraulic isolation all over azimuth radial. One effective way to detect the existence of channel is by using Cement Bond Log-Variable Density Log (CBL-VDL), an acoustic logging which is able to analyze quantitatively and qualitatively.